Role of MRI in the evaluation of spinal tuberculosis - M.R., Shashikumar; S.B., Basavaraj; Joshi, Vishwanath V.; C.P., Nanjaraj; N.L., Rajendrakumar (International Journal of Research in Medical Sciences, 2017)
Background: MRI is now the preferred imaging modality and preferred technique to define the activity and extent of infection for patients with suspected spinal tuberculosis. The objective of the study was to describe various radiological features of spinal tuberculosis (TB) on magnetic resonance imaging (MRI) and to assess its role in evaluation of the extent of disease. Methods: MRI images of 40 patients with proven Spinal Tuberculosis were retrospectively analyzed to determine the pattern of occurrence of various pathological lesions and extent of soft tissue involvement. Clinical features of the patients were also noted. Post-operative and follow up cases were excluded from the study. Results: The majority of the 40 patients were males (n=26) in the 31-40 years age group (50%). The most common clinical presentation was backache (77%) with a localized kyphotic deformity followed by fever (62.5%), malaise (47.5%) and weight loss (22.5%). The Thoracic spine was the commonest site of the disease (37.5%) followed by the thoracolumbar region (27.5%). An intervertebral disc involvement, pre and paravertebral collections, subligamental extension of the abscess were commonly seen, with an epidural collection occurring in more than 75 % of the cases. In addition few cases (n=5) also showed intramedullary and intradural involvement. Conclusions: The MRI scan is highly sensitive in the detection of various pathological processes of spinal tuberculosis and their pattern of occurrence. The extent of soft tissue involvement disease is best assessed by MRI which help in guiding the surgical treatment as well as to monitor the response to treatment during follow up.